The adoption and utilization of information and communication technology for the preservation and conservation of serial Publication in Lautech Medical Library and Lautech Teaching Hospital Library, Osogbo (2019)
The research was conducted to determine the adoption and utilization of ICT for Preservation and Conservation of serial publications in LAUTECH Medical Library and Lautech Teaching Hospital Library Osogbo. Four research questions were raised for this study. The research design used for this study is descriptive survey, the population of the study which constituted all library staff in these libraries were 35. Total population sampling method was employed in this study. The results were collated and analyzed using tables and percentages. It concludes that despite the low use of ICT for the serials functions, it has been shown to reduce the rigor in serials publication; ease of selection, acquisition and processing difficulties. Generally it has helped to reduce serials function and reduced the cost for acquiring serials. The work recommended that: university library funding bodies should provide adequate resources to libraries to enable them procure ICT facilities which have been proved to enhance serials accessibility; libraries which are .not using ICT facilities for serials functions should be encouraged to reposition their stand in order to provide the state of the art operations and services required by the present day serials users; and curriculum for library trainees should be expanded to accommodate the findings of this work.